EXAMINING THE IMPACT OF EASE OF USE, DATA SECURITY, AND USEFULNESS ON QRIS APPLICATION USAGE INTENSITY AMONG STUDENTS - Andriany, Dewy Rika; Nikensari, Sri Indah; Mukhtar, Saparuddin (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
This study aims to evaluate the influence of ease of use, data security, and usefulness on the usage intensity of the Quick Response Code Indonesian Standard (QRIS) application among students at the State University of Jakarta. This research employs a quantitative method with a survey approach. Data were obtained through questionnaires distributed to 150 students who have used the QRIS application. The sampling technique applied was convenience sampling. Data analysis was conducted using the Partial Least Square (PLS) method. The results of the study indicate that ease of use has a positive and significant influence on the intensity of QRIS application usage. Similarly, data security shows a positive and significant effect on usage intensity. Additionally, usefulness is found to have a positive and significant impact on the intensity of QRIS application usage among students at the State University of Jakarta. This study provides practical implications for QRIS application developers and stakeholders in the education sector to enhance features of ease of use, security, and usefulness to increase the usage intensity of the application among students.